Analysis of Physical Integrity Indicator on Environmental Sustainability in The Tourism Industry: Case Study in Padang Pariaman Regency - Nofriya Nofriya; Ahmad Fadhly (Program Pascasarjana Universitas Sriwijaya, 2021)
One of the development missions of Padang Pariaman Regency is to increase the potential for regional competitiveness through the development of tourism, transportation, trade, spatial planning, and environmental management. However, in the tourism policy has not seen the synergy of developing tourist destinations with environmental sustainability. This study evaluates physical integrity indicators in tourism activities in Padang Pariaman Regency to achieve environmentally sustainable development. This research uses a qualitative approach. Data were collected using in-depth interviews, document reviews, and observation of tourism objects. Data analysis was carried out by analyzing the themes and contents by triangulating the interviews' results, observing the results, and reviewing the documents. The results showed no special permit regarding environmental sustainability for tourism activities. However, each tourist attraction had its policy to protect the surrounding environment. The community is empowered to manage tourist objects and have local wisdom as a code of ethics in safeguarding the tourist area. The regional landscape is still preserved, but the beach's tourist objects are vulnerable to abrasion disturbances. It is recommended that the government make a policy to defend the physical integrity of the tourist attraction sites so that the concept of environmental sustainability can be achieved.